The Nutritional Intervention of Resveratrol Can Effectively Alleviate the Intestinal Inflammation Associated With Celiac Disease Induced by Wheat Gluten - Yu, Tian; Xie, Yiting; Yuan, Juanli; Gao, Jinyan; Xiao, Zhiwen; Wu, Yong; Chen, Hongbing (Frontiers in Immunology, 2022)
Background & Aims Wheat gluten is a critical trigger for celiac disease, often causing inflammatory lesions and oxidative stress damage in the intestines of patients. In daily life, it is difficult for celiac disease patients to strictly avoid the dietary intake of gluten, which makes complementary preventive therapy particularly urgent. As such, we investigated the alleviating effects of resveratrol in vivo and in vitro models of celiac disease. Methods We established in vivo and in vitro models of gluten protein-induced celiac disease, respectively. The intervention effect of resveratrol was defined well based on relevant indicators of inflammation, immunity and oxidative stress, and its possible involvement in signaling pathways and genes were also identified. Results Resveratrol was effective in reducing intestinal oxidative stress and inflammatory damage induced by wheat gluten in both cell and mouse models for celiac disease. We identified correlations between the genes (Fgf15, Nr0b2, Aire and Ubd) and signaling pathways (PPAR, AMPK and FoxO) in which resveratrol performed critical roles. Conclusions Resveratrol contributed to regulate development of autoimmunity through up-regulation of Aire and Ubd genes and promote nutrient absorption in intestine through down-regulation of Fgf15 and Nr0b2 genes, as well as played a role in regulating complex response system of oxidative stress, inflammatory response and immune response in intestine by activating PPAR, AMPK and FoxO signaling pathways, thus effectively alleviating the intestinal symptoms of celiac disease.